2005
DOI: 10.1093/ajcn/82.6.1178
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fatty acid composition is associated with the metabolic syndrome and low-grade inflammation in overweight adolescents

Abstract: Plasma FA composition is associated with weight status in healthy adolescents. High intake of long-chain PUFAs, especially n-3 PUFAs, may protect obese subjects against MS and low-grade inflammation as early as adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
197
6
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(229 citation statements)
references
References 33 publications
23
197
6
3
Order By: Relevance
“…9 Insulin resistance and adiposity have been characterized by an abnormal fatty acid pattern, including a high relative percent of palmitic, palmitoleic and dihomo-g-linolenic acids and low percent of linoleic acid in adults. 3,4,14,19,25,26 A similar pattern was observed in obese children in our study and others, 16,27 although study results have been inconsistent. 18 Desaturase activity Consistent with most previous studies of adults 4,11,14,28 and children, 16,18 we found that the estimated activities of D6 and D9 DAs were positively associated with adiposity and insulin measures in our study of adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…9 Insulin resistance and adiposity have been characterized by an abnormal fatty acid pattern, including a high relative percent of palmitic, palmitoleic and dihomo-g-linolenic acids and low percent of linoleic acid in adults. 3,4,14,19,25,26 A similar pattern was observed in obese children in our study and others, 16,27 although study results have been inconsistent. 18 Desaturase activity Consistent with most previous studies of adults 4,11,14,28 and children, 16,18 we found that the estimated activities of D6 and D9 DAs were positively associated with adiposity and insulin measures in our study of adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…82 It has been suggested that high dietary intake of specific fatty acids may stimulate IL-6 secretion, and, in contrast, high intakes of n-3 PUFAs may inhibit low-grade inflammation. 82,83 However, in the Swiss study, 56 total fat intake and percentage of energy from fat, and not specific types of dietary fat, predicted subclinical inflammation, independently of BMI.…”
Section: Subclinical Inflammationmentioning
confidence: 99%
“…81 Overweight adolescents with increased CRP and IL-6 concentrations have higher plasma saturated fatty acids and lower n-3 PUFAs compared with normal weight control participants. 82 It has been suggested that high dietary intake of specific fatty acids may stimulate IL-6 secretion, and, in contrast, high intakes of n-3 PUFAs may inhibit low-grade inflammation. 82,83 However, in the Swiss study, 56 total fat intake and percentage of energy from fat, and not specific types of dietary fat, predicted subclinical inflammation, independently of BMI.…”
Section: Subclinical Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the levels of EPA and DHA seen in the blood would have been far less than those seen in fish oil studies and purified EPA and/or DHA [20][21][22] delivering high amounts of EPA and DHA that apparently resulted in glycemic control deterioration in those studies. However as Klein-Platat et al 32) , and Phinney 33) have indicated it may be that blood levels of EPA and DHA may be inconsistent with tissues targeted by insulin for glucose uptake.…”
mentioning
confidence: 99%